ETHICS, SUBJECTIVITY AND THE SEARCH FOR JUSTICE: FEMININE OBJECTIFICATION AND THE CHALLENGES OF SOCIAL NORMS - Alves de Oliveira, Rose; Vinicius Lopes, Marcus (Revista Gênero e Interdisciplinaridade, 2024)
This article explores the relationship between the subject and the norm, addressing how ethics acts in the construction of individual subjectivity and in conflicts with social and legal norms, especially in contemporary issues such as the objectification of women on social media and civil disobedience. With an approach based on naturalist ethics and postmodern morality, and supported by the theories of Fraser (2007) and Fabriz (2003), the research investigates the effects of norms on mental health and fundamental rights, highlighting how the search for social recognition clashes with practices and structures that perpetuate oppression and patterns of behavior. The analysis criticizes objectification and the imposition of aesthetic and gender standards, defending an inclusive ethics that respects diversity and individual autonomy, thus promoting a more just and egalitarian society.